2007
DOI: 10.1051/0004-6361:20066967
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the innermost parsec of Centaurus A at mid-infrared wavelengths

Abstract: Context. To reveal the origin of mid-infrared radiation from the core of Centaurus A, we carried out interferometric observations with the MID-infrared Interferometer (MIDI) at ESO's VLTI telescope array. Aims. Observations were obtained with four baselines between unit telescopes of the VLTI, two of them roughly along the radio axis and two orthogonal to it. The interferometric measurements are spectrally resolved with λ/∆λ = 30 in the wavelength range 8 to 13 µm. Their resolution reaches 15 mas at the shorte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
151
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(166 citation statements)
references
References 46 publications
15
151
0
Order By: Relevance
“…The most promising tool for this task is IR interferometry, which was already successfully used for a number of nearby objects (Swain et al 2003;Wittkowski et al 2004;Weigelt et al 2004;Jaffe et al 2004;Poncelet et al 2006;Meisenheimer et al 2007;Tristram et al 2007Tristram et al , 2009Beckert et al 2008;Raban et al 2009;Burtscher et al 2009;Kishimoto et al 2009b). However, except for reconstructed images of NGC 1068 obtained from Speckle interferometry (Weigelt et al 2004), long-baseline interferometry usually provides spatial information coded as Fourier space observables, i.e.…”
Section: Interferometry Of Dust Torimentioning
confidence: 99%
“…The most promising tool for this task is IR interferometry, which was already successfully used for a number of nearby objects (Swain et al 2003;Wittkowski et al 2004;Weigelt et al 2004;Jaffe et al 2004;Poncelet et al 2006;Meisenheimer et al 2007;Tristram et al 2007Tristram et al , 2009Beckert et al 2008;Raban et al 2009;Burtscher et al 2009;Kishimoto et al 2009b). However, except for reconstructed images of NGC 1068 obtained from Speckle interferometry (Weigelt et al 2004), long-baseline interferometry usually provides spatial information coded as Fourier space observables, i.e.…”
Section: Interferometry Of Dust Torimentioning
confidence: 99%
“…This is possible since only the correlated spectrum depends on the projected baseline length and orientation and it is not expected that the N band source changes within one week. The 2005 observations that led to Meisenheimer et al (2007) were not included in this analysis since their total flux differs considerably from the 2008 observations. Finally, the calibrated correlated spectra were divided by the average single-dish spectrum to derive visibilities.…”
Section: Instrument Observations and Data Reductionmentioning
confidence: 99%
“…With limited (u,v) coverage, Meisenheimer et al (2007) found from earlier MIDI data that the mid-infrared (IR) emission from the central parsec of Centaurus A is dominated (60% at 13 mm) by an unresolved point source (diameter o10 mas). By comparison with multiwavelength data, this emission was classified as being most likely nonthermal (synchrotron) in origin.…”
Section: Introductionmentioning
confidence: 99%
“…early results on Seyfert 2 galaxies by Jaffe et al 2004; radio galaxy, Meisenheimer et al 2007; type 1 AGNs, Beckert et al 2008;Kishimoto et al 2009b;Burtscher et al 2009; snapshot survey, Tristram et al 2009). In the near-IR, after the very early results for the brightest Seyfert 1 galaxy NGC 4151 (Swain et al 2003) and Seyfert 2 galaxy NGC 1068 (Wittkowski et al 2004), long-baseline interferometry has now started to explore the innermost dusty structure extensively at milli-arcsec (mas) resolution (Kishimoto et al 2009a, hereafter Paper I; Pott et al 2010).…”
Section: Introductionmentioning
confidence: 99%